Modeling and Experimental Investigation of Monocrystalline Photovoltaic Module Performance under Derna Climate Conditions - Alhussien Almalh, Moftah Alshaikh, Mohamed Fargani, Fathi Lajhar, Yasser Aldali (Journal of Pure & Applied Sciences, 2020)
The aim of this paper is to examine the major impact of cell temperature on the performance of mono-crystalline module under Derna City climate conditions. A mathematical model was developed to estimate cell temperature where the method of energy balance is applied using meteorological parameters such as ambient temperature, slope radiation and wind speed. The experimental measurements were conducted for a particular day of October 2019. The validation of the calculated results was performed by comparing the attained results against measured cell temperature of the module. It was observed that the cell temperature, slope irradiance and electrical power output from the PV module reach the highest at 11:30, with values of 64.7 °C, 968 W/m2 and 47.73 W, respectively, whilst the ambient temperature found to be 36 °C. The energy balance method that presently deployed was highly successful in identifying the cell temperature, hence promising results of fitted parameters were of significance as the coefficient of determination (R2) = 0.9996, and the root mean square error (RMSE) = 0.582.